2007
DOI: 10.1111/j.1399-3038.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi‐Fujimoto disease of 16 children in a single center of Korea

Abstract: Kikuchi-Fujimoto disease (KFD) is subacute necrotizing lymphadenitis characterized by fever, leukopenia and cervical lymphadenopathy. There are few reports on the clinical characteristics and laboratory findings of KFD in the pediatric literature. In this study, we evaluate the characteristics and outcome of KFD in children. A total of 412 patients were studied with fever and peripheral lymphadenopathy at Pusan National University Hospital from January 1998 to December 2003. Among the total 412 there were 16 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…No studies have confirmed any positive serological findings relating to antinuclear antibodies, rheumatoid factors or other immunological parameters, as signs of the autoimmune nature of this disease. [1][2][3][9][10][11] Recent studies have demonstrated activated CD8+ cells after viral infection in lymph nodes, which may induce apoptosis of CD4+ lymphocytes. Hypothetically, apoptotic lymphocytes could deliver nuclear antigens and trigger autoimmune T and B cells to produce antinuclear antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No studies have confirmed any positive serological findings relating to antinuclear antibodies, rheumatoid factors or other immunological parameters, as signs of the autoimmune nature of this disease. [1][2][3][9][10][11] Recent studies have demonstrated activated CD8+ cells after viral infection in lymph nodes, which may induce apoptosis of CD4+ lymphocytes. Hypothetically, apoptotic lymphocytes could deliver nuclear antigens and trigger autoimmune T and B cells to produce antinuclear antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The lymph nodes are mainly small (less than 3 cm), mobile and painless. 3,6,7 Fever (usually high) is the first symptom in 30% to 50% of the cases; weight loss is observed in 10% and shivering in 4%. 7,9,14,15 Other less common manifestations include skin rash, gastrointestinal abnormalities and night sweating.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations